A metabolic investigation of arterialized venous flaps in rabbits using mass spectrometry‐based metabolomics. (26th March 2021) - Jin, Zeyuan; Luo, Xiaobin; Yuan, Kaizong; Lin, Damu; Cooper, Tokai Biggerboy; Yan, Hede
Abstract: An arterialized venous flap (AVF) is an ideal choice of flap to repair wounds. However, the survival of these flaps remains the source of some concern. This study used metabolomic analysis to investigate the mechanisms underlying survival in AVF flaps in order to guide the clinical application of these flaps. Thirty‐six male Japanese rabbits were randomly divided into a sham group and an AVF group. They were used for histology and hemodynamic investigations. Three days after surgery, tissue samples were analyzed by mass spectroscopy‐based metabolomics. The results of the study revealed a reduction in blood flow, infiltration of inflammatory cells, and necrosis of flaps in the AVF group. In addition, notable changes were evident in the levels of several metabolites in the AVF group, including lactic acid, acetoacetic acid, inositol phosphate, arachidonic acid, and other metabolites. Our results indicate that the AVF group experienced changes in several biological pathways, including energy metabolism, cell membrane stability, and inflammatory response. There is a significant metabolic difference between AVFs and physiological flaps. The dysregulation in certain metabolites may be related to the specific hemodynamics and insufficient energy metabolism of the AVFs.